A Desire To Regain The Lost Paradise – A Study OF A Novella “Sleepwalkers” BY Joginder Paul - Khera, Ayushi; Kashyap, Tanu (International Journal of Psychosocial Rehabilitation, 2020)
The paper attempts to focus on and analyse the trauma and the madness that an individual undergoes after the violent and the most deteriorating and disturbing situations that had occurred in the past. Primarily focusing on the novella “Sleepwalkers” by Joginder Paul, originally titled as “Khwabrau”, which is based on the post-partition trauma of India and Pakistan in 1947, the paper proposes to highlight the insanity that an individual suffers due to forced displacement triggered by the partition of the land. While underlining the insanity that the prime character of the novella named Deewane Maulvi Sahab suffers, the paper tends to look upon how the character in the novella attempts to make himself comfortable just by his own thoughts of having regained his ‘Paradise’ in his own mind and thus getting satisfied by it. It will further be analysed that the chaos initiated is not only present between the international borders of the newly formed countries India and Pakistan but is also present within the countries between the natives and the non-natives, who have been forced to leave their original homes and resettle into a totally different and new found land.